The value of victory in Pindar's odes : gnomai, cosmology and the role of the poet - Boeke, Hanna. (Mnemosyne, Supplements, 2007)
This book investigates the cosmological context of Pindar's victory odes, and how it influences his presentation of praise. The study first focuses on gnomai as a reflection of cosmology, using these sayings to establish the views the poems reveal on matters such as the divine, the human condition and man in society. This overview is complemented by detailed literary analyses demonstrating how cosmology functions in individual odes. They show that Pindar shapes the poet persona to emphasize different aspects of the traditional world view or represent varying viewpoints so that he can praise each victor according to his particular circumstances. By focusing on cosmology the book highlights a neglected dimension of Pindar's odes and challenges some traditional views on this poet.